Phenology and Availability of Fruit Trees and Their Influence on the Abundance of Selected Animalsi Logged and Primary Forest of Sungai Lalang Forest Reserve, Selangor - Jorge C. Lomoljo, Romeo M. Lomoljo (2003)
The abundance of fruit tree species as food source for wildlife in logged and primary forest was evaluated. The phenological data collection was carried out from September 1999 to October 2000 in Sungai lalang Forest Reserve, Semenyih. Selangor. Malaysia. The general objective of this study is to determine the fruit tree species that serves as food source for wildlife in logged and primary forest. The specific objectives are: to compare the availability of fruits to animals in three different compartments. To compare fruit trees distribution in three compartments within block. And to correlates the abundance of animals in relation to food availability. Three different Compartments were selected namely: Compartment 24 (VJR). Compartment 33 (10-year-old logged forest) and Compartment 18 (5-year-old logged forest). Within each Compartment, three blocks were established in different location (e.g. ridge top, midslope and valley bottom). All trees bigger than 10 em dbh were tagged and identified and monitored every month for leafing, flowering and fruiting activities. The Duncan's test indicated that the leafing pattern in Compartment 24 (VJR) was significantly different (P < 0.05) from Compartment 33 (10-year-old logged forest) and C ompartment 18 (5-year-old logged forest) (P < 0.05). The flowering pattern however, showed no significant differenc e among the three different Compartments. The percentage of fruiting was significantly lower in Compartment 18 (5-yearold logged forest) than in the pr imary f orest (VJR) (P <0.05).